Trends in the use of implantable cardioverter defibrillators in Australia: a 10‐year nationwide study from 2000–2009. Issue 8 (6th August 2013) - Burch, A. W. T.; Wong, C. X.; Sullivan, T.; Brooks, A. G.; Leong, D. P.; Lau, D. H.; Sun, M. T.; Roberts‐Thomson, K. C.; Sanders, P.
Abstract: Background: Implantable cardioverter defibrillators (ICD) have been demonstrated to reduce mortality in survivors of life‐threatening arrhythmias (secondary prevention) and in patients at increased risk of sudden cardiac death (primary prevention). Other nations have reported significant increases in ICD use in recent years. Aim: To investigate Australian nationwide trends of ICD procedures over a 10‐year period (2000–2009). Methods: A retrospective analysis of the Australian Institute of Health and Welfare's National Hospital Morbidity Database was performed to determine the annual number of ICD implantation and replacement procedures between 2000 and 2009. Rates were calculated using Australian Bureau of Statistics data on the annual estimated population. Time trends in the yearly procedure number and rate were analysed using negative binomial regression models with comparisons made by age and sex. Results: The number of new ICD implantations increased from 708 to 3198 procedures between 2000 and 2009. Replacement procedures increased from 290 to 1378. The implantation rate (per million) increased from 37.0 to 145.6 and the replacement rate from 15.1 to 62.7. When rates were adjusted for age and sex, the implantation rate increased annually by 15.8% and the replacement rate by 16.6% ( P < 0.0001). Procedures occurred most commonly in men (implantations: 80.1%; replacements: 78.0%) between ages 70–79. Conclusions: ICD procedures increased significantly in Australia between 2000–2009. Despite these increases, other studies have suggested ICD devices are currently under‐utilised. During the study period, males accounted for the majority of ICD procedures. While there are numerous reasons for this, it is not known if device under‐use is more common in females.